2014
DOI: 10.1177/0003489414543101
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Solutions in Head and Neck Cancer Surgery

Abstract: These data suggest a significant difference in the cytocidal effect of commonly used irrigation solutions on head and neck cancer cells in an in vitro model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…For head and neck cancer surgery, a preclinical efficacy study found that sterile water demonstrated a modest effect on cell survival, whereas 0.9% saline had no effect. 35 The addition of chemical adjuvants, such as 3% hydrogen peroxide, 0.05% chlorhexidine gluconate, and 0.3% povidone iodine solutions may reduce the burden of residual tumor cells. 36 However, further studies in vivo or clinical studies are required to assess its safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For head and neck cancer surgery, a preclinical efficacy study found that sterile water demonstrated a modest effect on cell survival, whereas 0.9% saline had no effect. 35 The addition of chemical adjuvants, such as 3% hydrogen peroxide, 0.05% chlorhexidine gluconate, and 0.3% povidone iodine solutions may reduce the burden of residual tumor cells. 36 However, further studies in vivo or clinical studies are required to assess its safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the saline washout is volume dependent and should be used copiously [20]. Furthermore, copious irrigation can keep the wound cavity clean and prevent infection, especially in aerodigestive tract [21,22]. Using this conservative treatment modality, the deciduous teeth and IAN can be preserved and the risk of recurrence as well as infection can be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] In head and neck cancer models, both the type of irrigation and type of cancer cell line contributed to efficacy. [ 18 , 19 ] These and other conflicting data suggest that multiple factors play a role with respect to the eradication of residual tumor burden, potentially related to the microenvironment and tumor cell-specific factors, such as cell adhesion properties and degree of de-differentiation.…”
Section: Discussionmentioning
confidence: 99%